At Westonci.ca, we provide clear, reliable answers to all your questions. Join our vibrant community and get the solutions you need. Experience the convenience of getting reliable answers to your questions from a vast network of knowledgeable experts. Get detailed and accurate answers to your questions from a dedicated community of experts on our Q&A platform.

If [tex]$a=\frac{-5}{6}$[/tex] and [tex]$b=\frac{3}{4}$[/tex],

Verify the following properties:

1. [tex]a + b = b + a[/tex]
2. [tex]a \times b = b \times a[/tex]


Sagot :

Let’s verify the given equations step by step.

### 1) Verify [tex]\(a + b = b + a\)[/tex]:

Given:
[tex]\[ a = \frac{-5}{6} \][/tex]
[tex]\[ b = \frac{3}{4} \][/tex]

First, we find [tex]\(a + b\)[/tex]:

[tex]\[ a + b = \frac{-5}{6} + \frac{3}{4} \][/tex]

To add these fractions, we need a common denominator. The least common multiple of 6 and 4 is 12. Thus:

[tex]\[ \frac{-5}{6} = \frac{-5 \cdot 2}{6 \cdot 2} = \frac{-10}{12} \][/tex]
[tex]\[ \frac{3}{4} = \frac{3 \cdot 3}{4 \cdot 3} = \frac{9}{12} \][/tex]

Now add the fractions:

[tex]\[ a + b = \frac{-10}{12} + \frac{9}{12} = \frac{-10 + 9}{12} = \frac{-1}{12} \][/tex]

Next, we find [tex]\(b + a\)[/tex]:

[tex]\[ b + a = \frac{3}{4} + \frac{-5}{6} \][/tex]

We already converted these fractions:

[tex]\[ \frac{3}{4} = \frac{9}{12} \][/tex]
[tex]\[ \frac{-5}{6} = \frac{-10}{12} \][/tex]

Now add them:

[tex]\[ b + a = \frac{9}{12} + \frac{-10}{12} = \frac{9 - 10}{12} = \frac{-1}{12} \][/tex]

Since:

[tex]\[ a + b = \frac{-1}{12} \][/tex]
[tex]\[ b + a = \frac{-1}{12} \][/tex]

We conclude that:

[tex]\[ a + b = b + a \][/tex]

### 2) Verify [tex]\(a \times b = b \times a\)[/tex]:

Given:
[tex]\[ a = \frac{-5}{6} \][/tex]
[tex]\[ b = \frac{3}{4} \][/tex]

First, we find [tex]\(a \times b\)[/tex]:

[tex]\[ a \times b = \frac{-5}{6} \times \frac{3}{4} \][/tex]

Multiply the numerators and the denominators:

[tex]\[ a \times b = \frac{-5 \cdot 3}{6 \cdot 4} = \frac{-15}{24} \][/tex]

Next, we find [tex]\(b \times a\)[/tex]:

[tex]\[ b \times a = \frac{3}{4} \times \frac{-5}{6} \][/tex]

Similarly, multiply the numerators and the denominators:

[tex]\[ b \times a = \frac{3 \cdot -5}{4 \cdot 6} = \frac{-15}{24} \][/tex]

Since:

[tex]\[ a \times b = \frac{-15}{24} \][/tex]
[tex]\[ b \times a = \frac{-15}{24} \][/tex]

We conclude that:

[tex]\[ a \times b = b \times a \][/tex]

So, both properties have been verified.
We hope our answers were useful. Return anytime for more information and answers to any other questions you have. We appreciate your visit. Our platform is always here to offer accurate and reliable answers. Return anytime. Get the answers you need at Westonci.ca. Stay informed with our latest expert advice.